Abnormal Reinnervation of Denervated Areas Following Nerve Injury Facilitates Neuropathic Pain - Hodaya Leibovich; Nahum Buzaglo; Shlomo Tsuriel; Liat Peretz; Yaki Caspi; Ben Katz; Shaya Lev; David Lichtstein; Alexander M. Binshtok (Cells, 2020)
An injury to peripheral nerves leads to skin denervation, which often is followed by increased pain sensitivity of the denervated areas and the development of neuropathic pain. Changes in innervation patterns during the reinnervation process of the denervated skin could contribute to the development of neuropathic pain. Here, we examined the changes in the innervation pattern during reinnervation and correlated them with the symptoms of neuropathic pain. Using a multispectral labeling technique—PainBow, which we developed, we characterized dorsal root ganglion (DRG) neurons innervating distinct areas of the rats’ paw. We then used spared nerve injury, causing partial denervation of the paw, and examined the changes in innervation patterns of the denervated areas during the development of allodynia and hyperalgesia. We found that, differently from normal conditions, during the development of neuropathic pain, these areas were mainly innervated by large, non-nociceptive neurons. Moreover, we found that the development of neuropathic pain is correlated with an overall decrease in the number of DRG neurons innervating these areas. Importantly, treatment with ouabain facilitated reinnervation and alleviated neuropathic pain. Our results suggest that local changes in peripheral innervation following denervation contribute to neuropathic pain development. The reversal of these changes decreases neuropathic pain.